2015
DOI: 10.2320/matertrans.m2015016
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Magnetite on Carbon Steel in Fe(III)-Triethanolamine Solution and Its Corrosion Behavior

Abstract: A dense and adhesive magnetite layer was successfully electrodeposited on a carbon steel in the Fe(III)-TEA solution. Electrochemical tests for the carbon steel and magnetite were conducted in an alkaline solution. These tests using the adherent magnetite specimens produced by electrodeposition is a new method to investigate the corrosion behavior of magnetite. The corrosion resistance of magnetite is superior to that of the carbon steel. When the magnetite and carbon steel are electrically contacted, the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Therefore, even if trace amount of Cu particles are present in the SG tube deposits, the Cu removal process should be included in the chemical cleaning process. As reported in many previous studies [4][5][6][7][8][9], this work again confirmed that magnetite accelerates the corrosion rate of SG materials by galvanic coupling. In addition, the results in this work had shown that metallic Cu and Pb as well as magnetite increased the corrosion rate of SG materials.…”
Section: Galvanic Coupling Sg Materials Galvanic Corrosion Parameterssupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, even if trace amount of Cu particles are present in the SG tube deposits, the Cu removal process should be included in the chemical cleaning process. As reported in many previous studies [4][5][6][7][8][9], this work again confirmed that magnetite accelerates the corrosion rate of SG materials by galvanic coupling. In addition, the results in this work had shown that metallic Cu and Pb as well as magnetite increased the corrosion rate of SG materials.…”
Section: Galvanic Coupling Sg Materials Galvanic Corrosion Parameterssupporting
confidence: 90%
“…Recently, many investigations on the galvanic effect by magnetite on the corrosion behavior of secondary coolant system materials such as nickel-based alloys [4][5][6] and carbon steel [7][8][9] have been reported. It is well known that the SG deposits mainly consist of magnetite and are porous in nature [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acceleration was due to the generation of hydrogen on the magnetite as well as the reduction of the magnetite itself in sulfate solution. 7) Jeon et al 8) reported that the corrosion rate of carbon steel coupled to magnetite increased by about 3.5 times than that of noncoupled carbon steel when they are contacted to the equivalent area ratio under alkalized reducing conditions of pH 9.5 which is a typical secondary water chemistry of PWRs.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in 2004, a pipe rupture accident occurred in the proximity of a flow-meter [7]. Aside from the wall thinning problem due to FAC, the corrosion rate of carbon steel piping with magnetite formation increases because magnetite is electrically contacted with carbon steel, resulting in a galvanic effect between the two materials [8,9].…”
Section: Introductionmentioning
confidence: 99%